Etiology, epidemiology and clinical characteristics of acute diarrhea in hospitalized children in rural Peru - Cornejo-Tapia, Angela; Orellana- Peralta, Fiorella; Weilg, Pablo; Bazan-Mayra, Jorge; Cornejo-Pacherres, Hernán; Ulloa-Urizar, Gabriela; Aguilar-Luis, Miguel Angel; Pons, Maria Jesus; del Valle-Mendoza, Juana (The Journal of Infection in Developing Countries, 2017)
Introduction: Diarrhea remains one of the main causes of morbidity and mortality in children under five years of age especially in low-income countries. In Peru, epidemiological reports about enteropathogens related to acute diarrhea are scarce in rural areas. The aim of this study was to describe the etiology, epidemiology, and clinical characteristics of the principal causes of acute infectious diarrhea in in a northern rural region of Peru. Methodology: A prospective study was conducted from January 2011 to December 2012 to describe the main pathogens causing acute diarrhea using PCR assay. Results: A total of 117 children diagnosed with acute diarrhea were included in the study. A single etiological agent was identified in 41.03% of samples, being rotavirus followed by norovirus and Shigella. Co-infections containing virus and bacteria were found in 22.22% of samples. Vomiting was most commonly found symptoms in 58.97% cases followed by fever (54.70%). Malnutrition was detected in 14.53% of the children. Conclusions: High prevalence of rotavirus, as well as adenovirus and norovirus, was observed in the present study. Shigella was the most common bacteria found in acute diarrhea in the area. The implementation of a better surveillance system is mandatory in order to identify the principal etiologies of gastroenteritis in the rural areas of Peru and to develop of better prevention strategies and reduce diarrhea-associated mortalities.